Towards Diversity in Global Journalism Studies. A Reply to Seth C. Lewis. Issue 2 (7th February 2022) - Raetzsch, Christoph; Ngomba, Teke; Olivera, Cecilia Arregui; From, Unni; Bødker, Henrik
Abstract: In a recent commentary, Seth Lewis calls for a "rethinking" of the "objects and objectives" of journalism studies in the wake of the COVID-19 pandemic. Whilst not underestimating the significant effects of this ongoing global health crisis, the authors of this commentary do not share the sense of urgency for revising the field on such a broad scale. We wish to raise three key points that criticize and supplement Lewis' reflections in light of existing debates in and beyond journalism studies and digital journalism studies in particular. These concern (1) the assumption that news journalism is relevant independent of its orientation towards audiences, an assumption that is problematized especially in digital journalism studies, (2) the overlooked importance of journalism education in a global perspective to create impact of research, and (3) the problematic assumption of a common identity of journalism studies scholars across the field as such. In this reply, the authors wish to make a pledge towards a greater importance of diversity in relation to global journalism studies and the importance of the field of digital journalism studies to realize such an ambition.